2018
DOI: 10.3390/su10030836
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors for Project Planning and Control in Prefabrication Housing Production: A China Study

Abstract: Abstract:The process of prefabrication housing production (PHP) has been inevitably faced with diverse challenges. A number of factors affect the successful implementation of PHP. However, the critical success factors (CSFs) remain unrevealed. This paper aims to examine the CSFs for the planning and control of PHP projects. A total of 23 factors were identified as a result of literature review, in-depth interviews and pilot studies with experts in the construction industry. A questionnaire survey was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 84 publications
(97 reference statements)
2
56
2
Order By: Relevance
“…Extant literature revealed that there is no universal CSFs identification method at present, and the selection of an appropriate method was based on the nature of the studies. For examples, Yang et al [51] employed an empirical survey to assess CSFs for build-operate-transfer projects, Li et al [52] used multiple methods to uncover CSFs for project planning and control in prefabrication housing production, and Olawumi and Chan [53] adopted a Delphi technique to investigate CSFs for building information modelling and sustainability practices. Considering all of the issues and the nature of the current study, a Delphi technique was employed as the method of inquiries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant literature revealed that there is no universal CSFs identification method at present, and the selection of an appropriate method was based on the nature of the studies. For examples, Yang et al [51] employed an empirical survey to assess CSFs for build-operate-transfer projects, Li et al [52] used multiple methods to uncover CSFs for project planning and control in prefabrication housing production, and Olawumi and Chan [53] adopted a Delphi technique to investigate CSFs for building information modelling and sustainability practices. Considering all of the issues and the nature of the current study, a Delphi technique was employed as the method of inquiries.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of the current study, CSFs allow the focused monitoring of factors that are critical to CSR adoption in Malaysian construction firms, from which appropriate actions can be taken to implement such practices within organizations. In the construction engineering management (CEM) literature, the CSFs approach has long been recognized and applied in many difference contexts, including, among others, build-operate-transfer projects [51], project planning and control [52], and building information modelling and sustainability practices [53].…”
Section: Critical Success Factors (Csfs)mentioning
confidence: 99%
“…From an academic perspective, this study divided the promotion areas into three groups on the basis of governmental guidelines and separately investigated their policy effectiveness. This idea is different from the methodology employed in previous studies (e.g., Jiang, Li, Li and Gao [9], Li, Li, Wu and Li [12] Mao, Shen, Pan and Ye [13]), which treated different areas in China as a single entity. The research findings of this study prove that the policy effectiveness in different areas could be inconsistent due to differences in the local economic or industrial conditions.…”
Section: Discussionmentioning
confidence: 92%
“…Based on an overview of the previous studies related to prefabrication incentive policies in China, it could be found that recent studies have mainly focused on policy identification and categorization [12]. However, the effectiveness of the current incentive policies has been questioned in previous research [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to manage them, CSFs were grouped in accordance with their relevance using factor analysis. The factor analysis can find the relationships among mutually related variables, understand these variables easily, and group them into common factors [41][42][43].…”
Section: Grouping the Csfs Using Factor Analysismentioning
confidence: 99%